Learning from the history of British interventions in the Middle East - Kettle, Louise (Edinburgh University Press, 2018)
Drawing on a wealth of previously unseen documents, sourced by Freedom of Information requests, together with interviews with government and intelligence agency officials, Louise Kettle questions whether the British government has learned anything from its military interventions in the Middle East, from the 1950s to the 2016 Iraq Inquiry report.